2010
DOI: 10.1007/s10802-010-9479-x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the Prospective Relationship Between Social Support, Stress, and Depressive Symptoms Among Adolescents

Abstract: The goal of the current study is to examine the relationship amongst social support, stress, and depressive symptoms within a transactional and diathesis-stress framework using a multi-wave, longitudinal design. At the initial assessment, adolescents (n = 258) completed self-report measures assessing social support (peer, classmate, parent, and total), dependent interpersonal stress, anxious symptoms, and depressive symptoms. Additionally, participants reported stress and symptomology in each of the four waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
119
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 58 publications
14
119
2
6
Order By: Relevance
“…O cuidado dos pais e o apoio familiar têm sido relacionados a resultados positivos no desenvolvimento dos adolescentes. Estudos evidenciam o quanto o apoio da família está ligado a menores índices de sintomas depressivos (Auerbach et al, 2011) e maior percepção de autoestima (Weber et al, 2010). Além disso, boa comunicação e apoio dos pais estão correlacionados ao menor envolvimento com álcool e drogas (Michael & Bem-Zur, 2007;Springer et al, 2006) já que ter relações positivas e estáveis entre pais e filhos pode possibilitar sentimentos positivos e maior afetividade nesse relacionamento, além de que o ambiente domés-tico passa a ser visto como agradável de conviver.…”
Section: Discussionunclassified
“…O cuidado dos pais e o apoio familiar têm sido relacionados a resultados positivos no desenvolvimento dos adolescentes. Estudos evidenciam o quanto o apoio da família está ligado a menores índices de sintomas depressivos (Auerbach et al, 2011) e maior percepção de autoestima (Weber et al, 2010). Além disso, boa comunicação e apoio dos pais estão correlacionados ao menor envolvimento com álcool e drogas (Michael & Bem-Zur, 2007;Springer et al, 2006) já que ter relações positivas e estáveis entre pais e filhos pode possibilitar sentimentos positivos e maior afetividade nesse relacionamento, além de que o ambiente domés-tico passa a ser visto como agradável de conviver.…”
Section: Discussionunclassified
“…However, other stud ies have failed to find support for the buffering hypothesis. In a 6-month prospective study of Canadian adolescents, researchers found that perceived parental support showed a main effect but not buffering effects against dependent negative life events on depres sive symptoms (Auerbach, Bigda-Peyton, Eberhart, Webb, & Ho, 2011). In fact, Burton, Stice, and Seeley (2004) argued that pro spective studies to date have shown almost no support for the buffering model (cf.…”
Section: Parental Support and Depressive Symptomsmentioning
confidence: 99%
“…For example, lack of parental support increases youth psychological distress (Auerbach et al 2010) while hostile, controlling or coercive parenting appears to heighten the likelihood that youth will be attracted to delinquent peers (Donovan and Jessor 1985;Metzler et al 1994;Williams et al 2008). Conversely, positive parent-child relationships play a central role in sustained positive outcomes for youth (Berzin 2010;Masten et al 1999;Repetti et al 2002).…”
Section: Family and Peer Relationshipsmentioning
confidence: 99%